IMPLEMENTASI MEDIA POWER POINT UNTUK MENARIK PERHATIAN SISWA PADA PEMBELAJARAN PAI MATERI AKIDAH AKHLAK DI SMP NEGERI 1 MARTAPURA - ahmad fuadi; Zulkifli, Muhammad (LP2M IAI Darussalam Martapura, 2023)
Abstrak.This research is motivated by the phenomenon of students' lack of interest and motivation in learning because in delivering material teachers rarely use learning media, especially PowerPoint, so it has an impact on student learning outcomes, even though LCDs are inadequate for using PowerPoint media. Based on this problem, teachers, especially PAI teachers, have the task of increasing students' attention to learning, one of which is through the use of power point learning media. In this case the author discusses the use of power point learning media in increasing students' attention studying at SMPN 1 Martapura.The focus of the research in this thesis is: (1) How is the use of power pointlearning media implemented in attracting the attention of class VIII students in the PAI subject of Aqidah Akhlak at SMPN 1 Martapura? (2) Supporting and Inhibiting Factors in using Power Point learning media in attracting the attention of class VIII students in the PAI subject of Aqidah Akhlak material at SMPN 1 Martapura?This type of research is field research with a qualitative approach. The subjects were 1 PAI teacher and 10 class VIII students at SMP Negeri 1 Martapura. The object is Power Point Media to Attract Students' Attention toLearning PAI Material on Moral Creeds for Class VIII at SMP Negeri 1 Martapura. Data collection techniques through observation, interviews and documentation. As for data processing techniques, namely editing, data classification and data interpretation. The data analysis used is qualitative descriptive analysis. namely in the form of a description and depiction of actual data. The results of this research show that the implementation of power point media is learning that has been used well because in accordance with the steps that have been explained it can attract students' attention during learning. Therefore, by using Power Point learning media, learning PAI Aqidah Akhlak material will attract students' attention. So that the impact of using PowerPoint learning media on students can increase learning motivation and stimulate learning activities and make learning more enjoyable.